Myocardial adipose deposition and the development of heart failure with preserved ejection fraction. (11th September 2019) - Wu, Cho‐Kai; Lee, Jen‐Kuang; Hsu, Jung‐Chi; Su, Mao‐Yuan M.; Wu, Yi‐Fan; Lin, Ting‐Tse; Lan, Chen‐Wei; Hwang, Juey‐Jen; Lin, Lian‐Yu
Abstract: Aims: It has been proposed that an increase of myocardial adiposity is related to left ventricular (LV) diastolic dysfunction. The specific roles of myocardial steatosis including epicardial fat and intramyocardial fat for diastolic function are unknown in those patients suffering heart failure (HF) with reduced (HFrEF) or preserved ejection fraction (HFpEF). This study aims to determine the complex relationship between myocardial adiposity in patients with HFrEF or HFpEF. Methods and results: Using cardiac magnetic resonance imaging (CMRI), myocardial steatosis was measured in 305 subjects (34 patients with HFrEF, 163 with HFpEF, and 108 non‐HF controls). We also evaluated cardiac structure and diastolic and systolic function by echocardiography and CMRI. Patients with HFpEF had significantly more intramyocardial fat than HFrEF patients or non‐HF controls [intramyocardial fat content (%), 1.56 (1.26, 1.89) vs. 0.75 (0.50, 0.87) and 1.0 (0.79, 1.15), P  < 0.05]. Intramyocardial fat amount (%) was higher in HFpEF women than in men [1.91% (1.17%, 2.32%) vs. 1.22 (0.87%, 2.02%), P  = 0.01]. When estimated by CMRI (left ventricular peak filling rate), echocardiographic E/e′ level, or left atrial volume index, intramyocardial fat correlated with LV diastolic dysfunction parameters in HFpEF patients, and this was independent of age, co‐morbidities, body mass index, gender, and myocardial fibrosis (standardized coefficient: β = −0.34, P  = 0.03; β = 0.29, P  = 0.025; and β = 0.25, P  = 0.02, respectively). Conclusions: Patients with HFpEF had significantly more intramyocardial fat than HFrEF patients or non‐HF controls. Independent of risk factors or gender, intramyocardial fat correlated with LV diastolic dysfunction parameters in HFpEF patients.